Interleukin-17 Cytokines and Receptors: Potential Amplifiers of Tendon Inflammation - Mimpen, Jolet Y.; Snelling, Sarah J. B.; Carr, Andrew J.; Dakin, Stephanie G. (Frontiers in Bioengineering and Biotechnology, 2021)
Interleukin (IL)-17A, a pro-inflammatory cytokine that is linked to the pathology of several inflammatory diseases, has been shown to be upregulated in early human tendinopathy and to mediate inflammatory and tissue remodelling events. However, it remains unclear which cells in tendons can respond to IL-17A, and how IL-17A, and its family members IL-17F and IL-17AF, can affect intracellular signalling activation and mRNA expression in healthy and diseased tendon-derived fibroblasts. Using well-phenotyped human tendon samples, we show that IL-17A and its receptors IL-17RA and IL-17RC are present in healthy hamstring, and tendinopathic and torn supraspinatus tendon tissue. Next, we investigated the effects of IL-17A, IL-17F, or IL-17AF on cultured patient-derived healthy and diseased tendon-derived fibroblasts. In these experiments, IL-17A treatment significantly upregulated IL6, MMP3, and PDPN mRNA expression in diseased tendon-derived fibroblasts. IL-17AF treatment induced moderate increases in these target genes, while little change was observed with IL-17F. These trends were reflected in the activation of intracellular signalling proteins p38 and NF-κB p65, which were significantly increased by IL-17A, modestly increased by IL-17AF, and not increased by IL-17F. In combination with TNF-a, all three IL-17 cytokines induced IL6 and MMP3 mRNA expression to similar levels. Therefore, this study confirms that healthy and diseased tendon-derived fibroblasts are responsive to IL-17 cytokines and that IL-17A induces the most profound intracellular signalling activation and mRNA expression of inflammatory genes, followed by IL-17AF, and finally IL-17F. The ability of IL-17 cytokines to induce a direct response and activate diverse pro-inflammatory signalling pathways through synergy with other inflammatory mediators suggests a role for IL-17 family members as amplifiers of tendon inflammation and as potential therapeutic targets in tendinopathy.